Threatened landscape in Alentejo, Portugal: the 'montado'and other 'agro-silvo-pastoral'systems (Landscape and Urban Planning, 1993)
In Portugal agro-silvo-pastoral systems correspond to the mixed land use types characteristic of the region of Alentejo, in the southern part of the country. There is a triple and complementary use of the land, adapted to the low potentialities of the soil and to the Mediterranean climate: open evergreen forest (oaks, olive and chestnut trees), grazing and cultivation. Due to their mixed characteristics and to the extensive form of exploitation, these systems constitute varied landscapes of high biological diversity. They have been managed through decades as an almost self-maintained system, with a minimum of human work input, but furnishing nevertheless the necessary outputs for the dispersed rural population of the area. Actually, due to the decrease in the economic value of some of the products concerned and to the changing context for Portuguese agriculture, these agro-silvo-pastoral systems have registered perturbations by intensification or extensification; in both cases there is a degradation or disappearance of the corresponding landscapes.